President's Message - Farley, Margaret; McKay, Marcy (Operating Room Nurses Association of Canada Journal, 2005)
I did bid farewell in my last President’s Message but, due to editorial deadlines, I was still the President when this letter was submitted. I thought I would take the opportunity to introduce the new ORNAC President. While Margaret will remain involved with the Executive, it will be in a more advisory role.